1991
DOI: 10.1002/ijc.2910480302
|View full text |Cite
|
Sign up to set email alerts
|

Liver cancer in Thailand. I. A case‐control study of cholangiocarcinoma

Abstract: Potential risk factors for cholangiocarcinoma were investigated in a case-control study among inhabitants of north-east Thailand, which included 103 cases from 3 hospitals, with age- and sex-matched controls. A clear association with past or present infection with Opisthorchis viverrini, as indicated by raised serum antibodies, was found (o.r. 5.0), and at least two-thirds of cases can be attributed to this cause. The results suggest that males may be at higher risk than females. There was no association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 13 publications
(12 reference statements)
7
124
1
Order By: Relevance
“…In this present study we found that those who have an OV antibody titre >23.337 compared with ≤23.337 have a higher risk for CCA (OR=3.09; 95%CI: 1.05-9.16). This positive finding is similar to those reported in other studies (Parkin et al, 1991;Honjo et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this present study we found that those who have an OV antibody titre >23.337 compared with ≤23.337 have a higher risk for CCA (OR=3.09; 95%CI: 1.05-9.16). This positive finding is similar to those reported in other studies (Parkin et al, 1991;Honjo et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…There was no association between smoking and risk of CCA in our study which is consistent with Parkin et al (1991), but not with Haswell-Elkins et al (1994).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although the incidence of ICC had been primarily associated with developing countries, ICC is now increasing in developed countries, especially in the United Kingdom and Japan (Kato et al, 1990;TaylorRobinson et al, 1997;McLean and Patel, 2006;West et al, 2006). Thailand has the highest incidence of ICC in the world, perhaps related to a tradition of eating raw fish, which may be contaminated with the liver fluke parasite, Opisthorchis viverrini, a cause of cholangiocarcinoma (Kurathong et al, 1985;Vatanasapt et al, 1990;Parkin et al, 1991;Thamavit et al, 1993;Sripa and Pairojkul, 2008). The prevalence of liver fluke infection in northeast Thailand is about 317.6 per 100,000 personyears (Sriamporn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%